Effects of Cocaine on Human Glial-Derived Extracellular Vesicles - Kumar, Sanjay; Matthews, Qiana L.; Sims, Brian (Frontiers in Cell and Developmental Biology, 2021)
Background: Microglia are important myeloid cells present in the brain parenchyma that serve a surveillance function in the central nervous system. Microglial cell activation results in neuroinflammation that, when prolonged, can disrupt immune homeostasis and neurogenesis. Activated microglia-derived extracellular vesicles (EVs) may be involved in the propagation of inflammatory responses and modulation of cell-to-cell communication. However, a complete understanding of how EVs are regulated by drugs of abuse, such as cocaine, is still lacking. Findings: Cocaine exposure reduced human microglial cell (HMC3) viability, decreased expression of CD63 and dectin-1 in HMC3-derived EVs, and increased expression of the apoptotic marker histone H2A.x in HMC3-derived EVs. Conclusion: Cocaine impacts HMC3 cells and EV protein expression, which could disrupt cellular signaling and cell-to-cell communication.